Prediction of Axial Load Carrying Capacity of RC Columns Retrofitted with Steel Jacketing - Gunarathna, K.C.S.; Kiriparan, B.; Kulathunga, D.D.T.K. (Society of structural engineers, sri lanka - annual sessions 2020, 2020)
Multi-storied building construction is one of the core component area in infrastructure development around the world. Addition and alteration to the existing buildings are involved commonly during the renovation of multistoried buildings. Overloading of existing columns beyond its carrying capacity is frequently encountered during the introduction of additional floors and alteration of intended floor function. Steel jacketing is one of the useful retrofitting techniques available for the strengthening of existing Reinforced Concrete Columns (RCC). Though steel jacketing is widely adopted internationally well-defined design provisions are not found in any of the design standards. The designs are either carried out using the provisions set out for composite columns or using experimental results. However, the behavior of the steel jacketed columns is significantly different from the composite columns. Further, various limitations are found even in the provisions given for composite columns. In the design of steel jacketing and composite columns width to thickness (b/t) ratio are limited to prevent local buckling of steel plate. Design provisions for slender sections are not covered in the international standards such as British and European standards. This paper intended to present the local buckling behavior and axial load carrying capacity of steel jacketed RCC columns using numerical simulations.